Understanding policy networks: towards a dialectical approach - Marsh, David; Smith, Martin (2000)
This article has two aims, First, we develop a dialectical model of the role that policy networks play in any explanation of policy outcomes. Our model is based upon a critique of existing approaches and emphasizes that the relationship between networks and outcomes is not a simple, unidimensional one. Rather, we argue that there are three interactive or dialectical relationships involved between: the structure of the network and the agents operating within them; the network and the context within which it operates; and the network and the policy outcome. Second, we use this model to help analyse and understand continuity and change in British agricultural policy since the 1930s. Obviously, one case is not sufficient to establish the utility of the model, but the case does illustrate both that policy networks can, and do, affect policy outcomes and that, in order to understand how that happens, we need to appreciate the role played by the three dialectical relationships highlighted in our model. - Reproduced
Keywords: Public policy